PENGARUH SOLVABILITAS TERHADAP AUDIT REPORT LAG DENGAN MEDIASI CORPORATE GOVERNANCE PADA PERUSAHAAN TAMBANG YANG TERDAFTAR DI BEI 2017-2018 - Efata Indri Tarigan; Joan Yuliana Hutapea (Program Studi Magister Manajemen Universitas Advent Indonesia, 2020)
The purpose of this study is to analyze the effect of solvency on the lag audit report with corporate governance as a mediating variable in companies listed on the Indonesia Stock Exchange for the period 2017-2018. Descriptive analysis will be used in this study and then processed using SPSS software. The sample in this study are: 20 (twenty) mining companies that listed on the Indonesia Stock Exchange for the period of 2017-2018. This study uses solvency as the dependent variable and audit report lag as an independent variable and corporate governance as a mediating variable. This study uses the square-R, t-significance, and regression analysis. The results of the analysis carried out in this study indicate that solvency has no significant effect on Audit Report Lag, Corporate Governance has a significant effect on Audit Report Lag, and Solvency has no significant effect on Audit Report Lag with the mediation of Corporate Governance.